Financial accounting from its basics to financial reporting and analysis - Spiteri, Simeon (Cambridge Scholars Publishing, 2020)
This book will appeal to individuals interested in developing their knowledge in financial accounting, including students sitting the Edexcel London exams, entrepreneurs and managers. It explains the process of recording transactions in depth by considering value added tax. The book adopts a practical approach, and highlights the main documents that lead to business transactions, while also describing accounting controls like bank reconciliation. In addition, the text addresses the main features and final accounts of different enterprises like sole trader, partnership, clubs and companies.